2008
DOI: 10.1002/jrs.1840
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Raman and IR spectra of non‐centrosymmetric PbB4O7 single crystal

Abstract: Polarized Raman and IR spectra of a PbB 4 O 7 single crystal were measured. The obtained spectra are discussed within the factor group approach for the orthorhombic P2 1 nm .C 2v 7 / space group with Z = 2 assuming that the crystal structure is built up of the (B 4 O 7 ) ∞ 2− framework and Pb 2+ ions. It has been shown that vibrations of borate and Pb 2+ units are observed above 240 and below 160 cm −1 , respectively. The results obtained for the spontaneous Raman scattering have also been used in the discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…reported on the vibrational properties of mirabilite, Na 2 SO 4 ‐10H 2 O and the rediscovered metastable heptahydrate, Na 2 SO 4 ‐7H 2 O . Polarized IR and Raman spectra of Na 3 Li(MoO 4 ) 2 ‐6H 2 O single crystal were measured by Hanuza and coworkers . The results for the spontaneous Raman scattering were used in the analysis of the stimulated Raman spectra of the material studied – a new Raman laser crystal.…”
Section: Solid‐state Studiesmentioning
confidence: 99%
“…reported on the vibrational properties of mirabilite, Na 2 SO 4 ‐10H 2 O and the rediscovered metastable heptahydrate, Na 2 SO 4 ‐7H 2 O . Polarized IR and Raman spectra of Na 3 Li(MoO 4 ) 2 ‐6H 2 O single crystal were measured by Hanuza and coworkers . The results for the spontaneous Raman scattering were used in the analysis of the stimulated Raman spectra of the material studied – a new Raman laser crystal.…”
Section: Solid‐state Studiesmentioning
confidence: 99%
“…Information about the symmetry of the modes is essential for understanding any phonon‐assisted phenomena such as structural transitions involving phonon softening or spin‐phonon coupling. Even origin of stimulated Raman scattering in PbB 4 O 7 is identified by a polarization‐dependent studies on single crystals . In the series RCrO 3 (R = La, Pr, Nd, and Sm), evolution of phonon wavenumber as a function of orthorhombic distortion and mode‐mixing behaviour was understood using assignment of vibrational modes by polarized Raman study.…”
Section: Introductionmentioning
confidence: 99%
“…Even origin of stimulated Raman scattering in PbB 4 O 7 is identified by a polarization-dependent studies on single crystals. [9] In the series RCrO 3 (R = La, Pr, Nd, and Sm), [10] evolution of phonon wavenumber as a function of orthorhombic distortion and mode-mixing behaviour was understood using assignment of vibrational modes by polarized Raman study. A detailed Raman and FTIR investigations on Na 2 Ti 3 O 7 enabled assignments of all the vibrational modes, which is useful for technological applications of the compound.…”
Section: Introductionmentioning
confidence: 99%
“…[146] Makreski and Jovanok [147] studied the mineral almandine originating from Macedonia and Ishibashi et al [148] reported on the relationship between the Raman spectral pattern and the crystallographic orientation of a rock-forming mineral Fo 89 Fa 11 olivine. Polarised Raman and IR spectra of non-centrosymmetric PbB 4 O 7 single crystals were investigated by Hanuza et al [149] Maczka et al [150] performed temperature-dependent Raman scattering studies of the geometrically frustrated pyrochlores Dy 2 Ti 2 O 7 , Gd 2 Ti 2 O 7 and Er 2 Ti 2 O 7 . Other temperature-dependent Raman scattering studies were carried out by Saraiva et al [151] on the Na 2 MoO 4 crystal and by Chiang et al [152] on iron perchlorate hexahydrate (Fe(ClO 4 ) 2 · 6H 2 O).…”
Section: Vibrational Studies In Chemistry (Combined Raman Infrared mentioning
confidence: 99%